Basic and translational evaluation of renewal of operant responding. Issue 2 (17th April 2015) - Kelley, Michael E.; Liddon, Clare J.; Ribeiro, Aurelia; Greif, Abigail E.; Podlesnik, Christopher A.
<x xml:space="preserve">Abstract</x> Treatment relapse, defined as the reemergence of problem behavior after treatment, is a serious difficulty faced by clinicians. Failures of treatment integrity (i.e., failure to implement interventions as intended) are often invoked to explain the reemergence of problem behavior. Basic studies suggest that the prevailing stimulus context might also contribute. We conducted 2 experiments in which reinforcement for a target response was followed by 2 phases of extinction with different or identical stimulus contexts relative to baseline (ABA renewal). In Experiment 1, pigeons served as subjects using procedures typical of those used in basic behavioral research. Experiment 2 was designed as a translational replication of Experiment 1, and children who had been diagnosed with autism served as participants. Returning to the previously reinforced stimulus context in both species produced a clear and immediate increase of extinguished responding. These findings are consistent with previous studies that have suggested that both reinforcement contingencies and stimulus context influence the reemergence of extinguished behavior.